The Rising Role of Individual and Society in the Development of International Security and the Advancement of Technology; a Southern Case Study - Aditya Pratama; Naifa Rizani Lardo; Togu Alexander (Institute of International Studies, 2019)
The emergence of Industrial Revolution 4.0 brings uncertainty in the development of InternationalRelations. In the context of international security, the south region is the epicentre of the development, especially with the concern of continual security issues that can be started or settled through the advancement of technology. However, the concept of International Security itself does not facilitate the change that currently occurs in the international world through industry 4.0. The role of the state is recognized as an upper hand over the role of individuals and society in international relations. Industrial Revolution 4.0 stresses the significance of autonomous and interconnectivity through advanced technology. On top of that, technology has been spread to the people globally. The existence of the internet helps people to expand their capacity as an individual. The aforementioned concept extends the role of individuals and society in international relations. This influence brings uncertainty to the traditional approach of International securitythus giving way for other viable approaches. This research utilizes the postmodernism approach as outlined by Jim George with a focus on the concept of Critical Social Movement by R.B.J. Walker to provide new insights for International Relations and security studies. This will be complimented several findings of security issues in the global south that illustrate the empowerment of individuals and society through the advancement of technology and their role in international security. With its emphasis on the role of individuals and society and its statement on the unpredictability of International Relations, this approach is, therefore, essential in comprehending the discourse of International Security in the era of industry 4.0.